Atividade queratinolítica de uma cepa de Streptomyces sp isolada de um abatedouro de aves - Oliveira, Gustavo Monteiro de [UNESP] (Universidade Estadual Paulista (Unesp), 2006)
Neste trabalho estudou-se a queratinase produzida por uma cepa de Streptomyces sp LMI-1 isolada de uma fábrica de processamento de aves domésticas. A enzima degradou 87% das penas após 120h de cultivo. Ela foi estimulada por íons Ba+2 e inibida por Ca+2, Mn+2, EDTA e Hg+. O pH ótimo de atividade da enzima foi 8,5 e a temperatura de maior atividade foi 60oC. A enzima é estável por até 2h em 50oC. Na análise do caldo de cultura detectou-se a presença dos aminoácidos serina, metionina, prolina, tirosina e leucina logo após 72h de cultivo. A enzima apresenta potencial para utilização industrial na produção de ração animal.

In the present work was studied keratinase produced by Streptomyces sp LMI-1 isolated of an industrial plant of poultry processing when cultived with feathers as a carbon source. The enzyme degraded 87% of feathers after 120 hours. The enzyme was stimulated by Ba+2 and inhibited by Ca+2, Mn+2, EDTA and Hg+. The optimum pH and temperature for the enzyme was 8,5 and 60oC, respectively. The enzyme was stable after 2 hours at 50oC. The culture broth analysis by thin layer chromatogram showed presence of amino acids serine, methionine, proline, tyrosine and leucine after 72 hours of incubation. The enzyme presents potential for industrial use in the production of animal feed preparation.
Keywords: Enzimas; Ração; Queratinase; Aminoácidos; Streptomyces; Keratinase; Enzyme; Amino acids